Associations between prenatal and recent postnatal methylmercury exposure and auditory function at age 19years in the Seychelles Child Development Study - Orlando, Mark S.; Dziorny, Adam C.; Harrington, Donald; Love, Tanzy; Shamlaye, Conrad F.; Watson, Gene E.; van Wijngaarden, Edwin; Davidson, Philip W.; Myers, Gary J. (Neurotoxicology and teratology, 2014)
The aim of this study was to determine if prenatal or recent postnatal methylmercury (MeHg) exposure from consuming ocean fish and seafood is associated with auditory deficits in young adults. Some investigators have reported adverse associations while others have found no associations. Ocean fish is an important nutrient source for billions of people around the world. Consequently, determining if there is an adverse association with objective auditory measures is important in assessing whether a risk is present or not. The peripheral and central auditory function of 534 subjects in the Seychelles Child Development Study (SCDS) Main Cohort was examined at age of 19years. The auditory test battery included standard pure-tone audiometry, tympanometry, auditory brainstem response (ABR) latencies, and both click-evoked and distortion-product otoacoustic emissions (OAE). Associations with MeHg were evaluated with multiple linear regression models, adjusting for sex, recent postnatal MeHg exposure, and hearing loss. Bilateral hearing loss (defined as a mean pure-tone threshold of greater than 25dB) was present in 1.1% of the subjects and was not associated with prenatal or recent postnatal MeHg exposure. As expected, absolute and interwave ABR latencies were shorter for women as compared to men, as the stimulus presentation rate decreased from 69.9 to 19.9 clicks/s and as the stimulus intensity increased from 60 to 80 dBnHL. Similarly, larger OAE amplitudes were elicited in women as compared to men and in the right ears as compared to the left. There was no association of prenatal MeHg exposure with hearing loss, ABR absolute and interwave latencies or OAE amplitudes. As recent postnatal MeHg increased, some associations were found with a few ABR absolute and interwave latencies and a few OAE amplitudes. However, the direction of these associations was inconsistent. As recent postnatal MeHg levels increased the wave I absolute latencies were shorter at 80 dBnHL for all three click rates, but the interwave I–V latency was longer for males for the 80 dBnHL 19 clicks/s and for the III–V interwave latencies for males and females for the dBnHL 69 clicks/s. Similarly, smaller OAE amplitudes were found at 1500, 2000, and 4000Hz for males while larger OAE amplitudes were found for females at 1500 and 2000Hz as the recent postnatal MeHg levels increased. No consistent associations were present in this study between prenatal MeHg exposure from consumption of oceanic fish and seafood during pregnancy and auditory functions at 19years of age. Given the level of prenatal exposure to MeHg, the number of audiologic measures tested, and the presence of the expected sex, click rate, and level dependent findings, it seems unlikely that an association was present and not detected. As recent postnatal MeHg exposure increased, a few associations with ABR latencies and OAE amplitudes were found. The direction of these associations was inconsistent as some showed improved performance as MeHg exposure levels increased while others showed poorer performance. The presence of the inconsistent postnatal MeHg exposure findings are intriguing and deserve further clarification.